In vitro activity of three commercial bacteriophage cocktails against multidrug-resistant Escherichia coli and Proteus spp. strains of human and non-human origin. (March 2017) - Bernasconi, Odette J.; Donà, Valentina; Tinguely, Regula; Endimiani, Andrea
Highlights: Bacteriophages represent a therapeutic alternative against MDR Enterobacteriaceae. Three commercial phage cocktails were tested against 101 E. coli and Proteus spp. isolates. E. coli susceptibility to PYO, INTESTI and Septaphage was 61%, 67% and 9%, respectively. Proteus spp. susceptibility to PYO, INTESTI and Septaphage was 29%, 39% and 19%, respectively. New phages need to be integrated in such preparations to target more MDR pathogens. Abstract: Objectives: Bacteriophages may represent a therapeutic alternative to treat infections caused by multidrug-resistant (MDR) pathogens. However, studies analysing their activity against MDR Enterobacteriaceae are limited. Methods: The in vitro lytic activity of three commercial bacteriophage cocktails (PYO, INTESTI and Septaphage) was evaluated against 70 Escherichia coli and 31 Proteus spp. of human and non-human origin. Isolates were characterised by phenotypic and genotypic methods and included 82 MDR strains [44 extended-spectrum-β-lactamase (ESBL)-producers (18 CTX-M-15-like, including ST131/ST648 E. coli ); 27 plasmid-mediated AmpC β-lactamase (pAmpC)-producers (23 CMY-2-like, including ST131 E. coli ); 3 ESBL + pAmpC-producers; and 8 carbapenemase-producers]. Phage susceptibility was determined by the spot test. Results: E. coli susceptibility to PYO, INTESTI and Septaphage was 61%, 67% and 9%, whereas that of Proteus spp. was 29%, 39% and 19%, respectively. For the subgroup of ESBL-producing E. coli / Proteus spp., the following susceptibility rates were recorded: PYO, 57%; INTESTI, 59%; and Septaphage, 11%. With regard to pAmpC-producers, 59%, 70% and 11% were susceptible to PYO, INTESTI and Septaphage, respectively. Five of eight carbapenemase-producers and three of four colistin-resistant E. coli were susceptible to PYO and INTESTI. Conclusions: This is the first study analysing the activity of the above three cocktails against well-characterised MDR E. coli and Proteus spp. The overall narrow spectrum of activity observed could be related to the absence of specific bacteriophages targeting these contemporary MDR strains that are spreading in different settings. Therefore, bacteriophages targeting emerging MDR pathogens need to be isolated and integrated in such biopreparations.